Turning calcined waste egg shells and wastewater to Brushite: Phosphorus adsorption from aqua media and anaerobic sludge leach water - Panagiotou, Evangelia; Kafa, Nasia; Koutsokeras, Loukas E.; Kouis, Panayiotis; Nikolaou, Petros; Constantinides, Georgios; Vyrides, Ioannis (My University, 2018)
Calcined egg shells are exploited for Phosphorus adsorption purposes and the resulting product is investigated for the purposes of transforming this waste material into a higher value product. The effect of particle size, calcination temperature (600 °C for 4 h, 800 °C for 2 h, and 900 °C for 30 min), and presence of ions (NO3−, NH4+, and CH3COOH) are investigated. Both, stock solutions prepared by dissolving anhydrous potassium dihydrogen phosphate (KH2PO4) with laboratory-grade water and wastewater from anaerobic digester effluent were used as Phosphorus containing aqua media. Calcined egg shells appear as an efficient material for phosphorous removal and their adsorption capacity increases as the calcination temperature increases and as the particle size reduces. This is attributed primarily to the increased specific surface area with calcination temperature as quantified through gas sorption and scan electron microscopy images. Egg shells calcinated at 900 °C for 30 min with particle sizes less than 1 mm exhibited the best performance among all material tested within this study. The presence of NO3− and NH4+ contributed positively to Phosphorus removal whereas the presence of CH3COOH supressed the Phosphorus removal process especially during the first 1 h; this effect is however reduced after 24 h. The experimental kinetic data were better represented with the non-linear form of the Langmuir isotherm and followed a pseudo-second-order model. Calcined egg shells that reacted with phosphorous in stock solutions or reject anaerobic sludge leached with H2SO4 transformed part into Brushite (CaHPO4·2H2O) as evidenced by X-ray diffractometry. The synthesis of Brushite under these conditions could be of great interest due to its high solubility (logKso = 6.59) and high Ca/P ratio that render it a potential fertilizer. This is the first study that notes the ecological production of Brushite using waste egg shells and anaerobic sludge as source materials.
Keywords: Anaerobic leached water; Brushite; Calcined egg shell; Circular bio-economy; Phosphorus adsorption